2006
DOI: 10.1073/pnas.0511325103
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, sequence-specific detection of unpurified PCR amplicons via a reusable, electrochemical sensor

Abstract: We report an electrochemical method for the sequence-specific detection of unpurified amplification products of the gyrB gene of Salmonella typhimurium. Using an asymmetric PCR and the electrochemical E-DNA detection scheme, single-stranded amplicons were produced from as few as 90 gene copies and, without subsequent purification, rapidly identified. The detection is specific; the sensor does not respond when challenged with control oligonucleotides based on the gyrB genes of either Escherichia coli or various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 36 publications
6
148
1
1
Order By: Relevance
“…13,24 In the absence of the target DNA, the sensor gives a sharp, well-defined ACV peak at ~260 mV (vs Ag/AgCl), consistent with the formal potential of the MB redox moiety used in this work ( Figure 1). Upon hybridization, binding-induced changes in the conformation of the stem-loop probe result in a decrease of the signal.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…13,24 In the absence of the target DNA, the sensor gives a sharp, well-defined ACV peak at ~260 mV (vs Ag/AgCl), consistent with the formal potential of the MB redox moiety used in this work ( Figure 1). Upon hybridization, binding-induced changes in the conformation of the stem-loop probe result in a decrease of the signal.…”
Section: Resultssupporting
confidence: 52%
“…For example, while it is likely that the signaling properties of these sensors depend sensitively on the density of immobilized probe DNA molecules on the sensor surface (measured in molecules of probe per square centimeter) [see, e.g., refs 5 and [29][30][31][32][33][34][35][36] ], no systematic study of this effect has been reported. Similarly, while it appears that the size of the target and the location of the recognition element within the target sequence affect signal suppression, 24 this effect, too, has seen relatively little study. Here we detail the effects of probe surface density, target length, and other aspects of molecular crowding on the signaling properties, specificity, and response time of the E-DNA sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this strategy, Lubin et al 43 successfully demonstrated an E-DNA sensor-based approach for detecting DNA authentication tags that are associated with paper or drugs. Lai et al 44 achieved the sequence-specific detection of unpurified amplification products of the gyrB gene of Salmonella typhimurium, which may open the path toward effective, field-portable sample-to-answer pathogen identification.…”
Section: Scaffolded Biosensors H Pei Et Almentioning
confidence: 99%
“…This E-DNA thus provides a costeffective and efficient technique for reagent-less and reusable detection of picomolar DNA, which holds great potential in medical and military applications. By using the E-DNA scheme, Lai et al [80] achieved sequencespecific detection of unpurified amplification products of the gyrB gene of Salmonella typhimurium, which may open the path toward effective and field-portable sampleto-answer pathogen identification.…”
Section: D Structured Dna Probesmentioning
confidence: 99%